2013
DOI: 10.5455/vetworld.2013.405-408
|View full text |Cite
|
Sign up to set email alerts
|

Physical and morphological characteristics of Kankrej bull semen

Abstract: Aim: Present investigation was carried out to study the physical characteristics of Kankrej bulls semen by evaluation of various semen parameters from neat semen and at various stages of semen preservation. Materials and Methods:A total of 60 ejaculates, 10 each from 6 mature Kankrej bulls, once in a week for 10 weeks, were collected and analyzed for various semen attributes. Result:The mean values for different seminal attributes were: ejaculate volume 4.84 + 0.01 ml, pH 6.88 + 0.01, mass motility 3.72 + 0.02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
11
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 2 publications
12
11
3
Order By: Relevance
“…The result got support from similar observations made by Kerur (1971) and Shelke and Dhami (2001)who reported the sperm concentration as 1250 and 1219.44 ± 38.24 million/ml in Gir bulls respectively. Similar values have also been found by various like Mandal et al, (2005), Raju and Rao (1982), Patel and Siddiquee (2013) in Shahiwal, Ongole and Kankeraj bull respectively. Such variations seem to be obvious as production od semen is highly specific traits and is influenced by various gentic and environmental factors.…”
Section: Sperm Concentrationsupporting
confidence: 88%
“…The result got support from similar observations made by Kerur (1971) and Shelke and Dhami (2001)who reported the sperm concentration as 1250 and 1219.44 ± 38.24 million/ml in Gir bulls respectively. Similar values have also been found by various like Mandal et al, (2005), Raju and Rao (1982), Patel and Siddiquee (2013) in Shahiwal, Ongole and Kankeraj bull respectively. Such variations seem to be obvious as production od semen is highly specific traits and is influenced by various gentic and environmental factors.…”
Section: Sperm Concentrationsupporting
confidence: 88%
“…45, 82.50±0.99, 87.08±0.76, 8.89±0.21, 85.60 ±1.04, 82.66± 0.70, respectively. In present study, mean value of mass activity of semen samples was in agreement with findings of some previous works done on bull semen (Patel and Siddiquee, 2013;Kumar and Krupakaran, 2014;Pande et al, 2015) but, higher than as reported by Kumar et al (2015). Average sperm concentration in present study was found to be comparable with some previous reports (Mandal et al, 2005;Patel and Siddiquee, 2013).…”
Section: Resultssupporting
confidence: 93%
“…The mean percentage of Individual progressive motility of semen samples was similar to findings of Pande et al (2015). However, higher Individual progressive motility has also been observed by Patel and Siddiquee (2013) and lowers by Kumar and Krupakaran (2014) and Kumar et al (2015). Sperm viability of a semen sample has direct and positive correlations with fertility of a bull.…”
Section: Resultssupporting
confidence: 69%
“…The reported results were in contrast to the results of current study. This indicates that the semen from Holstein Friesian bull, freezes in similar pattern to those of other breeds of cattle reared in hot season [27,28]. However, some contradictory reports were reported from different parts of the world.…”
Section: Membrane Integrity Test (Hot)mentioning
confidence: 79%